Effect of reaction temperature on the growth of carbon nanotubes from waste natural rubber glove - Hazan, Mohammad Adib; Mohamad, Syazwani; Hamid, Mohamad Amin; Shahira Liza; Mamat @ Mat Nazir, Md Shuhazlly; Chan, Kar Fei; Yaakob, Yazid (Universiti Putra Malaysia Press, 2020)
Natural rubber (NR) glove disposal is not environmentally appropriate and a range of approaches have been suggested to overcome the problem. Herein we indicate a simple method for producing high-value nanotubes from waste NR glove as a partial solution to the environmental problem. The laboratory-based waste NR glove was selected as a carbon precursor. Carbon nanotubes (CNTs) were synthesized using chemical vapor deposition (CVD) method comprising ferrocene over SiO2 substrate, which acted as a catalyst and surface for the carbon conversion process. The growth temperature was varied using 500, 600 and 700°C. The carbon precursor was analyzed using thermogravimetric analysis (TGA) to determine the optimum thermal decomposition of the waste. The CNTs collected after CVD process were analyzed using Raman spectroscopy, field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM). Optimization studies to determine the effect of temperature showed that the highest yield of CNTs was produced under a reaction temperature of 700°C (yield % = 5.47%, Raman ID/IG ratio = 0.82). The nanomaterials formed confirmed as CNTs and amorphous carbon under TEM images of the tubular structure of the products with a diameter range of 13 – 16 nm.